Odpowiedzi

Najlepsza Odpowiedź!
2010-03-22T15:33:25+01:00
2x+6=20
2x = 20 - 6 = 14
x = 14/2 = 7

23+9y = 50
9y = 50 - 23 = 27
y = 27/9 = 3

8y-36=24
8y = 24 + 36 = 60
y = 60/8 = 7,5

-4c-46=-2
- 4c = - 2 + 46 = 44
4c = - 44
c = - 44/4 = - 11

13+2x=3
2x = 3 - 13
2x = - 10
x = - 10/2 = - 5

-7=x+1
x = - 7 - 1 = - 8

2010-03-22T15:33:53+01:00
2x+6=20 /-6
2x=14 /: 2
x=7

23+9y = 50 /-23
9y=27 /:9
y=3

8y-36=24 /+36
8y=60 /:8
y=7i4/8

-4c-46=-2 /+46
-4c=44 /:4
c=11

13+2x=3 /-13
2x=-10 /:2
x=-5


-7=x+1 /-1
-8=x


2010-03-22T15:44:55+01:00
2x+6=20
2x=20-6
2x=14
x=7

23+9y = 50
9y=50-23
9y=27
y=3

8y-36=24
8y=24+36
8y=60
y=7,5

-4c-46=-2
-4c=-2+46
-4c=44
c=-11

13+2x=3
2x=3-13
2x=-10
x=-5

-7=x+1
-7-1=x
x=-8